2021
DOI: 10.3389/fpsyg.2021.660452
|View full text |Cite
|
Sign up to set email alerts
|

Narcissistic Leaders–Promise or Peril? The Patterns of Narcissistic Leaders’ Behaviors and Their Relation to Team Performance

Abstract: Leader narcissism has attracted substantial attention in leadership research and organizational practice. Yet, the exact relationship between leader narcissism and performance remains unclear. In this paper, we set out to illuminate the narcissism-leadership-performance puzzle. We build on research that points to a curvilinear relationship between leader narcissism and performance and open the black box behind this curvilinear relationship. Thereby, we take into consideration the context, in which narcissistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 128 publications
(198 reference statements)
0
5
0
Order By: Relevance
“…This type of leadership can have profound negative impacts on both individuals and organizations (Fatfouta, 2019). Research on narcissistic leadership has been growing in recent years as scholars seek to understand its implications and consequences (Schmid et al, 2021). One key issue in studying narcissistic leadership is the potential for negative outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…This type of leadership can have profound negative impacts on both individuals and organizations (Fatfouta, 2019). Research on narcissistic leadership has been growing in recent years as scholars seek to understand its implications and consequences (Schmid et al, 2021). One key issue in studying narcissistic leadership is the potential for negative outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, over time, the negative consequences of narcissistic leadership become apparent (Rosenthal and Pittinsky, 2006). Research has shown that narcissistic leaders are more likely to engage in unethical behavior, such as deception, manipulation, and exploitation of others for their own personal gain (Schmid et al, 2021). Yasir and Mohamad (2016) study recommends that senior management embrace and demonstrate ethical leadership, highlighting that ethical leadership is distinct in its focus on the moral and ethical dimensions of leadership behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Narcissism can be defined as a psychological state or a personality disorder that strives for a sense of self-worth, self-obsession, different feelings of entitlement, need for admiration, and other personality traits (Al-Abrrow et al, 2018;Yakeley, 2018). Narcissistic leaders always try to dominate their subordinates (Schmid et al, 2021). The concept of narcissism is also considered a pattern that revolves around oneself and self-importance because this pattern is also linked with abnormality (Germain, 2018b).…”
Section: Introductionmentioning
confidence: 99%